Scintigraphic correlates of discourse impairment in dementia with Lewy bodies - Kluj-Kozłowska, Klaudia; Sitek, Emilia J.; Brockhuis, Bogna; Wieczorek, Dariusz; Lass, Piotr; Sławek, Jarosław; Milewski, Stanisław; Domagała, Aneta (Logopedia Silesiana, 2021)
In the clinical presentation of dementia with Lewy bodies (DLB), speech and communication disorders coexist with cognitive deficits. Discourse is impaired both at the syntactic and lexical levels. The aim of this study was to demonstrate the existence of scintigraphic correlates with lexical and syntactic errors in the patients’ narrative speech. Twelve patients with DLB participated in the study. Analysis shows relationships between selected aspects of narrative discourse in DLB and cerebral hypoperfusion. It has identified correlations between lexical and syntactic impairment of speech and hypoperfusion within temporal, parietal and occipital areas, both in left and right hemisphere. The ability to create narrative speech on the basis of complex pictorial material requires the engagement of the perceptual function, which may explain the relationship between discourse impairment and posterior, in particular right-sided, hypoperfusion.